RECONSTRUCTION OF ARTICLE 62 OF LAW NUMBER 13 OF 2003 ON EMPLOYMENT REGARDING THE RULES ON COMPENSATION IN THE TERMINATION OF A FIXED-TERM EMPLOYMENT AGREEMENT THAT IS FAIR - Desman, Yose; Zainal Arifin Hoesein (Ikatan Dosen Menulis, 2025)
Article 62 of Law Number 13 of 2003 concerning Manpower requires compensation to be provided by the party terminating the employment relationship in a Fixed-Term Employment Agreement (PKWT) before the end of the agreement period. This provision, although intended as a form of protection for workers, creates an imbalance for employers, especially if the termination is carried out for legitimate reasons or force majeure. This study aims to reconstruct the provision so that it reflects substantive justice for both parties and is relevant to the national legal reform agenda. The method used is normative juridical with a statutory regulatory approach, a conceptual approach, and a comparative legal approach. The results of the study indicate the need for a new formulation of Article 62 that considers proportionality, reasons for termination, and the principle of equality in industrial relations. The proposed reconstruction prioritizes contractual flexibility and balanced protection, in line with the spirit of national legal reform to create a responsive, fair, and sustainable employment system.